Spring Sings for the Grouchy Ladybug - Carle, Eric; Zegar, Rachel; Penguin Random House; World of Eric Carle (Firm) (New York, NY : Harper, an imprint of HarperCollinsPublishers, 2023)
"Celebrates the new life that blossoms during spring. The animals are playing outside, the flowers are blooming, and everyone is joyous--even The Grouchy Ladybug"--
Keywords: Spring -- Juvenile fiction; Animals -- Juvenile fiction; Ladybugs -- Juvenile fiction; Spring -- Fiction; Animals -- Fiction; Ladybugs -- Fiction; Picture books; Picture books